Impact of important ICAR-CISH technologies - S C, Ravi; Raghav, Dushyant Kumar; Damodaran, T; Beer, Karma; Gupta, Alok Kumar (Indian Horticulture, 2026)
The ICAR-Central Institute for Subtropical Horticulture, Lucknow has pioneered the development and dissemination of varieties and technologies to enhance productivity, quality, and marketability of fruits in Subtropical region of the country. The impact of CISH developed guava varieties Lalit and Shweta, technologies such as ICAR FUSICONT, CISH Metwash and the effect of cluster-based programs was evaluated. Adoption of varieties have led to increased yield, adoption of ICAR FUSICONT increased the productivity, adoption of GAP led to decreased use of chemicals and increased exports besides promoting entrepreneurship, and generated significant economic benefits. The study underscores the importance of large-scale adoption of these varieties and technologies to maximize economic and social benefits for all stakeholders.